Analisis Model dan Strategi Pembelajaran Prosa pada Pembelajaran Hikayat di SMK Negeri 4 Medan - Kaila Azzahra Yasmin; Chintia Lafaezah Sihaloho; Filomena Nova Julianti Sinurat; Erfanintiya Siringoringo; Tesalonica Evelin Br Sitorus; Kezia Tarila Rubina Br Sitepu; Safinatul Hasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the models and strategies of prose teaching, specifically Hikayat, at SMK Negeri 4 Medan. The teaching of prose plays a significant role in enhancing students' literacy, deepening appreciation for literary works, and instilling moral and local cultural values. The method used in this study is descriptive qualitative, which includes observation, interviews, and documentation, with an emphasis on the implementation of teaching strategies by Indonesian language teachers. The results of the study show that the learning process at this vocational school faces various challenges, such as low student interest and limitations in literacy. To address these issues, teachers integrate theory with practice, utilize multimedia-based technology, and implement group discussions to encourage active student participation. Evaluation is conducted through student work presentations, combining literacy assessment and speaking skills. Recommendations from this study include the development of innovative, technology-based approaches and increased student engagement in the learning process to create more effective and meaningful learning experiences.